The Implementation of The Social Penetration Theory in Da'wah Communication - Nurmala, Nurmala; Prasongko, Wahyu Agung (STAI Publisistik Thawalib Jakarta, 2024)
Dakwah invites towards goodness through effective communication. The social penetration theory builds intimate relationships, enhances message acceptance, and creates positive impacts for the audience (mad’u). This study analyzes the application of social penetration theory in da’wah communication to improve the effectiveness and interpersonal relationships between the da’i and mad’u. The research uses a descriptive qualitative approach with literature review, examining social penetration theory in da’wah communication by collecting data from books, journals, and relevant articles. The findings show: In the orientation stage, the da’i introduces themselves and provides basic religious information to establish an initial connection. In the exploratory affective exchange stage, the da’i opens up, sharing more personal values and religious messages, creating emotional closeness. In the affective stage, the da’i shares personal experiences and life challenges, deepening understanding and trust. In the stable stage, the relationship becomes more honest and intimate, with efficient communication, strengthening the acceptance of religious messages.